Combined use of DSC, TGA, XDR and NIR in the compatibility study of preformulation mixtures for the development of 10 mg tablets of Rupatadine Fumarate - Castillo Henríquez, Luis (2018)
It is essential to guarantee physico-chemical compatibility between the active pharmaceutical ingredient (API) and the components that are planned to be used in the development of a pharmaceutical formulation. A successful compatibility study allows distinguishing between the excipients that can be used and those that may represent a risk in the quality, safety and efficacy of the medication. The present study focuses on the identification of possible incompatibilities between Rupatadine fumarate and the excipients of three formulation prototypes for the development of API´s 10 mg tablets. Samples of each raw material, placebos and preformulation mixtures were analyzed by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), X-ray diffraction (XDR) and infrared spectroscopy (IRS). The results obtained were analyzed and contrasted with the literature. Based on these, it is demonstrated that the excipients used along with the API do not generate problems in terms of compatibility, as there are no chemical changes in the drug.